Social responsibility and its role in enhancing the quality of services: an analytical study of the views of a sample of employees in the Directorate of Electricity Distribution Nineveh / Center - حسين, بشار غانم (Journal of Economics and Administrative Sciences, 2020)
The current research aims to diagnose the role of social responsibility as a contributing factor in enhancing the quality of services provided by the public sector in Iraq, where the research sought to demonstrate the relationship and impact of social responsibility dimensions (economic, legal, moral, and human) on the sector Services related to the electric field in Nineveh governorate because of its importance and its direct relationship with the citizen especially after the end of military operations in the destruction of the electricity sector by a large percentage in the city of Mosul. Nineveh Electricity Distribution Directorate / Center was chosen as a research community including (administrators and staff) of the researched organization and the distribution of (40) form prepared for this purpose to indicate the opinion of the research sample on the research variables (social responsibility and quality of services) and relied on the statistical program (SPSS) to reach the results, which supported the problem and hypotheses of research in acceptable proportions. The research also reached a set of conclusions and proposals, which confirmed the adoption of the research organization of the research variables.